Survey in social rsearch - Vaus David de (London Routledge, 2002)
This fifth edition of a bestselling textbook has been completely rewritten to include new examples and data focusing on technology, the use of qualitative and quantitative methods together, and the importance of data analysis within sociology.
Keywords: Social sciences-research